Diffuse Toxic Goiter Hyperthyroid with Atrial Fibrillation in Type 2 Diabetes Patient - Alif Ridhani (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Goiter is an enlargement of the thyroid gland which can occur in euthyroid, hyperthyroid, or hypothyroid. Hyperthyroidism can cause symptoms, such as palpitations, fatigue, sleep disturbances, weight loss, and heat intolerance. There are various complications and symptoms of hyperthyroidism, one of which is cardiac arrhythmia. Thyroid dysfunction can coexist with type 2 diabetes, so special attention is needed. Male, 43 years old, complaining of palpitations in the chest since 2 days ago. Complaints were accompanied by weakness, hand tremors, and lack of appetite. Patient also complained there was a lump in the neck that moved when swallowing since 5 months ago. Patient has a history of type 2 diabetes and regularly takes metformin. Physical examination found diffuse enlargement of the thyroid gland, soft consistency, indistinct borders and irregular heart rhythm. Electrocardiography showed atrial fibrillation. Ultrasound examination revealed bilateral diffuse goiter. Free T4 result is elevated. Therapy given is infusion, methimazole, beta-blockers, digoxin, and metformin. Thyroid hormones have significant effects on the heart, which include increasing resting pulse rate, blood volume, stroke volume, cardiac muscle contractility, and ejection fraction. Thyroid also causes sinus rhythm disturbances. Early thyroid treatment has a better prognosis for improvement. Treatment of hyperthyroidism can affect the condition of diabetes, so monitoring blood sugar is necessary. Early diagnosis and prompt treatment of hyperthyroidism can resolve complaints and prevent complications. Thyroxine concentrations higher than normal are more at risk of experiencing atrial fibrillation. Hyperthyroidism can occur together with type 2 diabetes so it needs special attention.